Adapting fiscal polities for the Covid 19 pandemic. Setting up a fiscal system appropriate for the digital world - Lilian ONESCU; Daniela FLORESCU (Smart Cities and Regional Development Journal)
In the current context generated by the Covid 19 pandemic, Member States need secure tax revenues to invest in people and businesses affected by the health crisis. At the same time, we need to remove the tax barriers and make it easier for EU businesses to innovate, invest and grow. To achieve this, in July 2020, the EU Commission adopted the Action Plan, which includes measures to reduce the administrative burdens, improve tax compliance and combat fraud. The Action Plan is helping to create a more fair, easier tax system to be used and adapted to our digital world. In case of this article there were used tools like as: classification, synthesis, comparative analysis, induction and deduction methods, graphic representation of events and investigated phenomenons. The article is addressed to the university and the academic world, as well as to fiscal administration officials and to the decision-making factors for correcting inequalities, created by the Covid 19 pandemic.